PENGARUH MEREK, KUALITAS PRODUK, HARGA TERHADAP NILAI PRODUK DAN DAMPAKNYA TERHADAP MINAT BELI RAMBAK KULIT IKAN - 11.42.02.0095, Lilies Kushandini (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study was to examine the effect of Brand, Product Quality, Price on the Product Value and its impact on Interests Buying Rambak Fish Skin. This research was conducted on consumers rambak fish skin in the district Batang with infinite population. Sampling technique using purposive sampling, with the criteria established by the requirement that consumers who have bought the fish skin rambak least 1 time purchase products rambak fish skin, and is domiciled in the district of Batang many as 100 people and statistical method are used to test the validity of the components of matrix, test reliability with cronbach alpha, multiple regression analysis, t test and the adjusted r square R2.The results reveal that the Brand has a positive effect with beta value = 0.000 and no significant effect on the Product Value rambak fish skin in the district Batang (sig = 0.994> 0.05). Product Quality has a positive effect with a beta value = 0.212 and significant 0.032 <0.05 on the Product Value rambak fish skin in the district Batang. Price has a positive effect with a beta value = 0.691 and significant 0.000 <0.05 on the Product Value rambak fish skin in the district Batang. Brands has a positive effect with a beta value = 0.103, and not significant 0.233> 0.05 on Buying Interest in the district Batang. Product Quality has a positive effect with beta value = 0.153 and not significant 0.168> 0.05 on Buying Interest. The Price has a positive effect and significant beta value of 0.303 with significant value of 0.012 <0.05 on Buying Interest, a positive effect the Product has Value beta 0.359 and significant Buying Interest with a significant value of 0.000 is less than 0.05. The Product Value does not mediate the effect of the Interest in Buying the Brand, the Product Value does not mediate the effect of the Interest in Buying the Product Quality, the Product Value does not mediate the effect of Price on Purchase Interest. Keywords: Brand, Product Quality, Price, Products Value, Buy Interests.